Effects of Gamma Irradiation on the Properties of Hydroxyapatite-Collagen-Chitosan-Mg-ZnO Scaffolds for Bone Tissue Engineering - Tusher -Al-Arafat; Shawon Ahmed; Polash Chandra Karmakar; Umme Salma Zohora; Naznin Akhtar; S. M. Asaduzzaman (International Journal of Polymer Science)
Bone tissue engineering aims to repair diseased or damaged bone that cannot be regenerated naturally. This study is designed to develop biodegradable porous scaffolds as bone substitutes and evaluate the effect of gamma irradiation on these scaffolds for the restoration of defected bone. Here, composite scaffolds (HA-COL-CS-Mg-ZnO) were prepared by the thermally induced phase separation (TIPS) technique using collagen (COL) and chitosan (CS), hydroxyapatite (HA), magnesium (Mg), and zinc oxide (ZnO) at different mass ratios. Thereafter, the scaffolds were subjected to 10 KGy γ-radiation for physical cross-linking and sterilization. The physicochemical and biological properties of the scaffolds were evaluated by Fourier transform infrared spectroscopy-attenuated total reflectance (FTIR-ATR), field emission scanning electron microscopy (FESEM), physical stability (biodegradability, swelling rate, porosity, and density), mechanical properties, biocompatibility, cytotoxicity, and antimicrobial activity against Escherichia coli (ATCC-25922) and Staphylococcus aureus (ATCC-25923). We found that the irradiated scaffold showed enhanced tensile strength and antimicrobial activities which are desirable characteristics of bone-mimicking scaffolds. FESEM revealed that the average pore size decreased from 192.3 to 104.5 μm due to radiation. FTIR-ATR spectra showed that γ-radiation triggered cross-linking in the polymer matrix which improved mechanical strength (0.82 N/mm2 to 1.86 N/mm2) by increasing pore wall thickness. Moreover, the irradiated and nonirradiated scaffolds were biocompatible and noncytotoxic toward the Vero cell line which ensured their suitability for use in vivo. These results demonstrate that sterilization of HA-COL-CS-Mg-ZnO scaffolds with gamma-irradiation substantially improves the physicochemical and morphological features which aid bone tissue regeneration and could be supportive for new bone formation.